1999
DOI: 10.1074/jbc.274.50.35845
|View full text |Cite
|
Sign up to set email alerts
|

Brain Actin-associated Protein Phosphatase 1 Holoenzymes Containing Spinophilin, Neurabin, and Selected Catalytic Subunit Isoforms

Abstract: We previously characterized PP1bp134 and PP1bp175, two neuronal proteins that bind the protein phosphatase 1 catalytic subunit (PP1). Here we purify from rat brain actin-cytoskeletal extracts PP1 A holoenzymes selectively enriched in PP1␥ 1 over PP1␤ isoforms and also containing PP1bp134 and PP1bp175. PP1bp134 and PP1bp175 were identified as the synapse-localized Factin-binding proteins spinophilin (Allen, P. B., Ouimet, C. C., and Greengard, P. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 40 publications
6
105
1
2
Order By: Relevance
“…Neurabin II belongs to this class of regulators because it negatively regulates the PP1 catalytic subunit activity. Native neurabin II associates with PP1 (44). DCX, neurabin II, and PP1 are found in the same protein complex when PP1 is pulled down with PP1-specific microcystin-agarose beads and also when DCX is immunoprecipitated from mouse brain extracts (31).…”
Section: Discussionmentioning
confidence: 96%
“…Neurabin II belongs to this class of regulators because it negatively regulates the PP1 catalytic subunit activity. Native neurabin II associates with PP1 (44). DCX, neurabin II, and PP1 are found in the same protein complex when PP1 is pulled down with PP1-specific microcystin-agarose beads and also when DCX is immunoprecipitated from mouse brain extracts (31).…”
Section: Discussionmentioning
confidence: 96%
“…47 SPN selectively interacts with PPP1CC in the spinal cord, and it has been suggested that this binding is, at least in part, responsible for the enrichment of PPP1CC at synapses. 48 Similarly, the binding of SPN to PPP1CA results in partial coupled regulation between SPN and PP1a, as lower levels of SPN led to decreased PPP1CA Figure 4 (See opposite page). Loss of Spn increases p53 activity.…”
Section: Discussionmentioning
confidence: 98%
“…Nuclear extract (5 g) was incubated in phosphatase buffer (20 mM Tris-HCl (pH 7.0), 1 mM DTT, 0.1 mM EGTA, 2 mM MgCl 2 , 1ϫ protease inhibitor mixture solution (Roche Molecular Biochemicals)) at 4 or 30°C for the indicated period of time. The MIN6 nuclear extract was incubated at 30°C in phosphatase buffer with CIAP (0.25 l/reaction (10-l reaction mixture volume); 20 units/l (Promega)) or BPP catalytic subunit mixture (1 l/reaction (10 l), 360 fmol/min using glycogen phosphorylase (31)). The brain protein phosphatase catalytic subunitenriched preparation was prepared by ethanol precipitation of a rat brain soluble extract (31).…”
Section: Methodsmentioning
confidence: 99%